2016
DOI: 10.1007/s10661-016-5174-x
|View full text |Cite
|
Sign up to set email alerts
|

Element distribution over the surface of fish scales and its connection to the geochemical environment of habitats: a potential biogeochemical tag

Abstract: The elemental content of fish scales is known to be a reliable biogeochemical tag for tracing the origin of fishes. In this study, this correlation is further confirmed to exist on the surface of fish scales using a novel environmental analytical method, laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS), which bypasses several complicated sample preparation procedures such as acid digestion and pre-concentration. The results suggest that the elemental ratios of Sr/Ca, Ba/Ca, and Mn/Ca on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…In contrast to scale shapes, which can be mediated both by genetic and environmental influences, scale chemistry can equally serve as a biogeochemical tag [17,18,26,37] and a pollution bioindicator of the habitat [38], as the hydroxyapatite or apatite-(CaOH) layer of scale can accommodate a wide range of elements directly from seawater [39]. In addition, several authors have noted the temporal stability and/or low rates of post-depositional alterations of scale-derived apatite of anadromous species [18,26,37,40], which allows correct fish classification back to their original environment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast to scale shapes, which can be mediated both by genetic and environmental influences, scale chemistry can equally serve as a biogeochemical tag [17,18,26,37] and a pollution bioindicator of the habitat [38], as the hydroxyapatite or apatite-(CaOH) layer of scale can accommodate a wide range of elements directly from seawater [39]. In addition, several authors have noted the temporal stability and/or low rates of post-depositional alterations of scale-derived apatite of anadromous species [18,26,37,40], which allows correct fish classification back to their original environment.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that, for both marine and freshwater systems, the elemental ratio on the surface of fish scales is closely related to aquatic environment in which the fish grew up [38,46]. This is particularly significant for trace-elements such as Sr, Ba and Mn.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of a laser offers also the possibility of performing an in-depth scanning, exploiting the progressive ablation of the material which occurs when the laser is fired several times on the same position [9][10][11]. One of the techniques of election for this kind of elemental mapping is the Laser-Ablation Inductively Coupled Plasma Mass Spectrometry (LA-ICP-MS) [12][13][14][15][16] which allows for high resolution 3D elemental mapping of materials, with high sensitivity and isotopic resolution. However, LA-ICP-MS instruments are complex and very expensive, and the procedure leading to elemental mapping can be long and suffer of artefacts [17,18]; this fact has triggered the research of simpler and more affordable methods for elemental 3D mapping that could be extremely interesting for application in which high sensitivity and isotopic information are not a priority.…”
Section: Introductionmentioning
confidence: 99%